PENINGKATAN PEMBELAJARAN TAHFIDZ AL-QUR’AN MENGGUNAKAN METODE QUR’ANI SIDOGIRI - Makhrus Ali, M.; Makhrus Ali, Solehati; Qurotul Ahyun, Faizah (As-Sulthan Journal of Education, 2025)
The purpose of this research is to find out how far students learn the Qur’an, the most important thing is in understanding and studying the Qur’an using the Sidogiri Qur’ani method and in memorizing the Qur’an propely and correctly. In applying the sidogiri Qur’ani method here the author uses the students at the Tahfidz At-Taqwa 2 House, totaling 11 students as the main object of this study, so that they can find out more about the process and developmet of these students. In studying and memorizing the Qur’an properly and correctly. Reading and memorizing the Qur’an is not just reading, but also being able to understand and understand the meaning and content of the Qur’an. And it must be precise and correct both in terms of pronunciatiom, makharijul letter, and also the tajwid. The Sidogiri Al-Qur’an method is not just an ordinary method, but in this method it is explained in more detail how to pronounce hijaiyah letters properly and correctly. As well as being taught about the various types of tajwid and given examples and how to differentiate them. And also the Sidogiri Qur’an method is more inclined to rhythm, so that in this method there is a rhythmthat makes the students more interested in learning the koran. In memorizing the Al-Qur’an students are more enthusiastic in memorizing the verses of the Al-Qur’an, because according to students this method makes it easier to remember and lear the Al-Qur’an.